An Idea of Taxation: The Perspective Of The Islamic Tradition - Siti Maisyarah Syahar; Dewi Angela Kusuma Fortuna; Sitti Humaerah; Fadhilah Diwani Azzahra Nawir (Academic Bright Collaboration, 2024)
In most countries, the tax is one of the main foreign exchange to support the success of national development so that a collection that has a logical consequence in the life of society, nation and state as a reflection of a justice for welfare. The tax charged to every citizen who has the obligation to pay taxes. Entering the new millennium, Muslims are concered with historical expectations as well as formidable challenges especially on economic issues. In Islam there is a group of people obliged to issue a small part of his property as alms that they were already categorized capable to tithe. Called zakat because it contains the hope of obtaining a blessing, cleanse the soul and nuruture it with various virtues. Zakat and tax are two obligations at the same time for religion and the state. Zakat and tax are two obligations which are equally obligatory on Muslims.